The Effect of Mathematics Teacher Performance and Student Attitude to Mathematics Teacher toward Student Mathematics Reasoning Ability - Isnawan, Muhamad Galang (International Conference on Elementary Education, 2020)
The low of mathematics reasoning ability is one of student problem. This is caused by mathematics teacher performance and student attitudes to mathematics teacher. Therefore, this study aims to describe the effect of mathematics teacher performance and student attitudes to mathematics teachers toward student mathematics reasoning ability. This type of research is ex-post facto. The population of this study was all mathematics teachers and students public junior high school on east praya about 264 people with a sample of all mathematics teachers and students at 3rd east praya public junior high school about 72 people (purposive random sampling). The instruments used in this study were teacher performance questionnaire, student attitude questionnaire, and mathematics reasoning ability test. The statistical test used to analyze the data is a regression test (F-test and t-test). Based on the research results obtained information that t about 42,574 with a significance of 0,000 (H01 rejected); t about 40,243 with a significance of 0,000 (H02 rejected); and F about 1,763 with a significance of 0,000 (H03 rejected). Therefore, it can be concluded that mathematics teacher performance and student attitude to mathematics teacher have a significant effect on student mathematics reasoning ability (individually and together)